Clastic Sedimentology of the Beaufort Formation, Prince Patrick Island, Canadian Arctic Islands: Late Tertiary Sandy Braided River Deposits With Woody Detritus Beds - Devaney, Jonathan R. (ARCTIC, 1991)
The Beaufort Formation (probably of Pliocene age) exposed on Prince Patrick Island in the western Canadian Arctic Islands is an unlithified and poorly exposed unit consisting of the following assemblage of facies; (A) clast-supported gravel (channel floor lags, longitudinal bars); (B) cross-bedded sand (transverse bars, channel floor dunes); (C) rippled sand; (D) horizontally laminated fines - mixed sand, silt and woody detritus; (E) clay-rich mud (overbank suspension deposits); and (F) woody plant detritus, beds of flat-lying logs, sticks, twigs, wood chips, bark, leaves, needles, seeds, and moss (overbank suspension and traction deposits). Minor facies include pebble bands, plane laminated sand, and a thin bouldery basal gravel horizon. The sediments are interpreted to be sandy braided river deposits that are notable for their regionally abundant beds of course woody detritus, a feature uncommon in most ancient braided fluvial deposits. Facies A to C represent bar and channel deposits, with Facies B the most abundant. Facies C to F are relatively minor and are interpreted as low-stage overbank deposits such as abandoned channel fills. Rapid, small-scale lateral facies changes are the norm. Well-defined fining-upward sequences 1.2-2.5 m thick are uncommon. The relative rarity, thinness, and lateral impersistence of overbank facies compared to bar-channel facies suggests that significant amounts of meandering river deposits are not present. The common allochthonous woody fossils were sourced from boreal forests nearby. A thin horizon in one stratigraphic section contains tidal bundles with slack water mud drapes. The Beaufort sediments exposed on Prince Patrick Island appear to be the most proximal portion of a northwest-(offshore-) thickening clastic sheet. The eroded upper surface of the Beaufort Formation, of regional extent on the western arctic coastal plain, is covered with a highly polymict gravel lag that is far coarser and compositionally more diverse than gravel within the Beaufort Formation. Beaufort ...